A medium-strength and high-thermal-conductivity titanium-based composite material and a preparation method thereof
By generating TIC and/or TIB as a enhanced body by reaction in the titanium base, combined with the cold and vacuum sintering process of cold and vacuum, the medium -sized high -conducting thermal titanium base composite materials are prepared, which solves the heat conduction and strength of the materials in the existing technology. The difficulty of balanced problems achieved efficient and low -cost preparation technology.
Patent Information
- Application Number
- CN202310072555.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-07
AI Technical Summary
In the prior art, titanium-based composite materials that use graphene reinforcement have problems such as high preparation process requirements, high cost and low thermal conductivity, and it is difficult to meet the balance of the properties of medium and high thermal conductivity.
By generating TIC and/or TIB as a enhanced body by reaction in the titanium base, combined with cold pressure and vacuum sintering process, the yield strength is 605 ~ 750MPa, and the thermal guidance rate at 100 ° C is 15.5 ~ 19w/(m M M M · K) medium -sized high -guide thermal titanium base composite material.
The intensity of the material and the balance of thermal conductivity have the high yield strength, good thermal conductivity and high extension rate, and the process is simple, the cost is low, suitable for large -scale production.
Smart Images

Figure CN116240426B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal-based composite materials, and in particular to a medium-strength and high-thermal-conductivity titanium-based composite material and a preparation method thereof. Background Art
[0002] Titanium alloy materials have the characteristics of good corrosion resistance, good plasticity and toughness matching, high specific strength and biocompatibility. Titanium alloys are widely used in aerospace, medical, chemical and shipbuilding fields. In particular, titanium alloys have good corrosion resistance and long comprehensive life. Titanium heat exchangers have been widely used in chemical and marine fields. However, pure titanium TA2 heat exchangers are currently more commonly used. The thermal conductivity can reach 20W / (m·K) at 100℃, but the strength of pure titanium materials is relatively low, and the yield strength Rp is 0.2 It is only 270MPa. In the marine environment, under certain high environmental pressure conditions, the yield strength of pure titanium cannot meet the application requirements, and its strength needs to be improved.
[0003] The traditional method to improve the strength of titanium alloys is to add other types of metal elements to alloy them. When the yield strength is increased to above 500MPa, the thermal conductivity of the currently commonly used national standard titanium alloys is usually less than 12W / mK at 100°C. For example, the typical medium-strength titanium alloys Ti70 and Ti75 used in the shipbuilding and marine fields have yield strengths of 600MPa and 630MPa, respectively, and their thermal conductivity at 100°C is only 10W / m·K, which is only about half of the thermal conductivity of pure titanium. The thermal conductivity of the material is proportional to the heat transfer efficiency of the heat exchanger, and a decrease in thermal conductivity will directly reduce the heat transfer efficiency. Patent CN 109136645 A discloses a new type of titanium alloy with low density, high thermal conductivity and high strength, and specifically contains the following components: Li: 2.0-2.5wt.%, Mg: 6.0-8.0wt.%, Ag: 1.5-2.0wt.%, In: 2.0-3.5wt.%, Hf: 0.5-1.0wt.%, Cr: 0.8-1.2wt.%, Fe: 1.0-1.4wt.%, Ta: 0.2-4.0wt.%, and the balance is Ti. The heat transfer coefficient of this titanium alloy material is as high as 85-92W / (m·K), but this material contains a large number of corrosion-resistant alloy components, such as Ag, Fe, Cr, etc., which are prone to corrosion in long-term use in marine environments, and use a large number of rare earth alloy elements such as In, Hf, Ta, etc., resulting in high material costs and difficult to promote and apply. Patent CN111763849A proposes a method for adding graphene reinforcement into a titanium alloy matrix to prepare a titanium-based composite material, which can improve the strength of the material while improving its thermal conductivity. The prior art increases the thermal conductivity of the material by adding a graphene content range of 2 to 20%, controlling the graphene not to react with the matrix titanium. Although the strength of the material is improved, the plasticity is reduced; at the same time, the price of graphene is relatively high, and a large amount of addition will significantly increase the cost of the material, and in order to control the graphene not to react with the matrix, its sintering process needs to be strictly controlled; especially when the thermal conductivity of the material prepared by the prior art is finally 9.5W / (m·K) when the addition amount reaches 5%, the thermal conductivity is still low, and the elongation is only about 12%. Therefore, the titanium-based composite material reinforced with graphene in the prior art has high preparation process requirements, high cost, low thermal conductivity, and it is difficult to meet the balance of medium strength and high thermal conductivity. Summary of the invention
[0004] In view of this, the present invention aims to propose a medium-strength and high-thermal-conductivity titanium-based composite material and a preparation method thereof, so as to solve the problems of the existing graphene-reinforced titanium-based composite materials, such as high preparation process requirements, high cost, low thermal conductivity, and difficulty in achieving a balance between medium-strength and high thermal conductivity.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A medium-strength and high-thermal-conductivity titanium-based composite material comprises a reinforcement and a pure titanium matrix, wherein the reinforcement is produced by an in-situ autogenous reaction between a composite phase and a pure titanium matrix, the size of the reinforcement is 10 nm to 10 μm, the size of the pure titanium matrix is 10 to 50 μm, the volume fraction of the reinforcement is 1 to 4%, the yield strength of the medium-strength and high-thermal-conductivity titanium-based composite material is 605 to 750 MPa, the thermal conductivity at 100° C. is 15.5 to 19 W / (m·K), and the elongation is 10 to 18%.
[0007] This setting improves the strength of the material by adding in-situ self-generated reinforcements. At the same time, the reinforcements also serve as a conductive medium to increase thermal conductivity. Controlling the content of the reinforcements reduces grain boundaries and phase boundaries, reduces the scattering of phonons at the interface, and increases thermal conductivity.
[0008] Furthermore, the reinforcement is TiC and / or TiB, and the reinforcement is formed by the reaction of a composite phase and the pure titanium matrix.
[0009] Furthermore, the composite phase is selected from one or a mixture of TiB2, graphene, graphite, carbon nanotubes, B4C.
[0010] A method for preparing a medium-strength and high thermal conductivity titanium-based composite material, preparing the above-mentioned medium-strength and high thermal conductivity titanium-based composite material, comprising the following steps:
[0011] Step 1: According to the mass ratio of composite phase powder to titanium powder of 0.3-1.0:99.7-99.0, the two powders are mixed evenly by vacuum ball milling;
[0012] Step 2: Put the mixed powder into a rubber bag, seal it and put it into a cold isostatic press to form a green body through a cold isostatic pressing process;
[0013] Step 3: Transfer the formed green body into the vacuum sintering furnace quickly and evacuate to 10 -1 ~50Pa, followed by sintering, during which the vacuum state is maintained;
[0014] Step 4: After the sintered material cools down in the furnace, it is taken out;
[0015] Step 5: further densifying the sintered material.
[0016] The preparation method of the present invention uses simple ball milling combined with cold isostatic pressing and vacuum sintering to prepare medium-strength and high thermal conductivity titanium alloy materials, has low requirements on equipment, simple process and low cost, and is conducive to subsequent large-scale production.
[0017] Furthermore, the average particle size of the composite phase powder is 30 nm to 3 μm, and the particle size range of the titanium powder is 10-50 μm.
[0018] Furthermore, the composite phase is selected from one or a mixture of TiB2, graphite, carbon nanotubes, B4C.
[0019] Furthermore, the vacuum ball milling is performed on any one of a drum ball mill, a planetary ball mill or a vibration ball mill. The vacuum ball milling uses a polyurethane ball milling jar, the grinding balls are ZrO2 grinding balls, and the ball-to-material ratio is 2 to 4:1.
[0020] Furthermore, the rotation speed of the ball mill is set to 150-350 rpm, and the process of the ball mill is specifically set to rotate clockwise for 20-40 minutes, pause for 10-20 minutes, then continue to rotate counterclockwise for 20-40 minutes, pause for 10-20 minutes, and cycle in this sequence. The cumulative effective ball milling time is 5-10 hours.
[0021] Furthermore, the molding pressure of the cold isostatic press is set to 180-280 MPa, and the holding time is set to 30-180 s.
[0022] Furthermore, the time from the end of cold isostatic pressing to the transfer of the green body into the vacuum sintering furnace is controlled within 10 to 60 minutes, the sintering temperature is set to 950 to 1080° C., and the sintering time is set to 1 to 10 hours.
[0023] Furthermore, the sintered material may be further subjected to a densification treatment, wherein the densification treatment is any one of die forging, hot rolling or hot isostatic pressing.
[0024] Furthermore, the titanium powder is prepared by a hydrogenation-dehydrogenation method, has an irregular shape, and has an oxygen content of 0.15 to 0.22 wt.%.
[0025] This setup uses hydrogenation and dehydrogenation as the raw titanium powder, which can reduce the cost of raw materials on the one hand, and on the other hand, the irregularly shaped powder is easier to press into a green body with higher density, and the sintered material as a matrix has higher strength. The oxygen content of the powder cannot be too high, otherwise it will easily increase the brittleness of the material.
[0026] Compared with the prior art, the medium-strength and high-thermal-conductivity titanium-based composite material and the preparation method thereof described in the present invention have the following advantages:
[0027] 1) The present invention prepares a titanium-based composite material with a yield strength of 605-750MPa, a tensile strength of 705-800MPa, and a thermal conductivity of 15.5-19W / (m·K) at 100°C by adding TiC and / or TiB reinforcements in an in-situ autogenous manner and by reasonably matching the size of the reinforcements with the matrix pure titanium. At the same time, the density of the titanium-based composite material is 4.49-4.52g / cm 3The elongation is as high as 10-18%, which can meet the requirements of subsequent processing, deformation and other processes of the material.
[0028] 2) The TiC and TiB reinforcements selected by the present invention, first of all, have a low thermal expansion coefficient, and will not produce a large stress concentration when reacting with the matrix titanium. Secondly, the theoretical thermal conductivity of TiC and TiB is higher than that of pure titanium. Therefore, the generated reinforcement can also be used as a heat transfer medium to promote heat conduction. Finally, TiC and TiB are self-generated in situ, and have good interface bonding with the matrix, which can ensure good transmission under stress, improve material strength, and reduce phonon scattering to ensure good heat conduction. At the same time, the volume fraction of the reinforcement needs to be controlled between 1 and 4% to prevent excessive reinforcement from being added, resulting in the formation of a brittle network structure and destroying the plasticity of the material. At the same time, by controlling the particle size matching of the raw materials, on the one hand, the composite phase can be better mixed with the matrix titanium powder to avoid agglomeration and uneven composition, and reduce the generation of defects; on the other hand, the size of the reinforcement finally generated can be controlled to be within a suitable range, so as to achieve a high level of strength and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the composite material prepared in Example 1 of the present invention;
[0030] Figure 2 for Figure 1 Magnified view of the organization;
[0031] Figure 3 It is a stress-strain curve diagram of Examples 1-4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0033] The titanium alloy grades currently used lack medium-strength and high thermal conductivity titanium alloys, which limits the use of titanium alloys in situations where higher strength and better thermal conductivity are required. The use of graphene-enhanced titanium-based composite materials has the problems of high preparation process requirements, high cost, and low thermal conductivity, and it is also difficult to meet the balance of medium strength and high thermal conductivity. Therefore, the present invention proposes a medium-strength and high thermal conductivity titanium-based composite material and a preparation method thereof, which achieves a balance between the mechanical properties and thermal conductivity of the material by designing the components, and obtains a medium-strength and high thermal conductivity titanium alloy material with high strength, good thermal conductivity, good plasticity, and easy processing.
[0034] Example 1
[0035] Use electronic balance to weigh 6.0g B4C powder and 994.0g hydrogenated dehydrogenated titanium powder respectively, the average particle size of B4C powder is 500nm, the particle size range of hydrogenated dehydrogenated titanium powder is 10-50μm, and the oxygen content of the selected titanium powder is 0.21wt.%. Weigh zirconia grinding balls, weight 3kg, zirconia grinding balls are composed of four different sizes of grinding balls with diameters of 1mm, 3mm, 5mm and 10mm, so that the powders can be mixed more fully. The two weighed powders are quickly transferred to a polyurethane vacuum ball milling jar and vacuum-sealed to prevent the increase of oxygen content. Afterwards, they are installed on a planetary ball mill for ball milling, the speed of the planetary ball milling is set to 150rpm, and the ball milling program is set to rotate clockwise for 20min, pause for 10min, then switch to rotate counterclockwise for 20min, pause for 10min, and then rotate clockwise for 20min, cycle in this order, and the effective ball milling time is accumulated to 5h. Setting the forward and reverse rotation can ensure that the powder is fully mixed evenly, and setting the pause time can dissipate the heat of the ball mill to avoid excessive energy accumulation in the ball mill, resulting in cold welding, agglomeration, etc., which will cause uneven powder mixing. After the ball milling is completed, the powder is sieved, the grinding balls are removed, and the powder is sealed and packaged to isolate oxygen and avoid oxidation.
[0036] The ball-milled powder was placed in a rubber bag, sealed, and then cold isostatically pressed at a pressure of 180 MPa for 30 seconds. After the cold isostatic pressing, the green body was quickly transferred to a vacuum sintering furnace within 10 minutes and evacuated to 10 -1 Pa. Then heating started, and insulation started after the temperature reached 1050℃, and the insulation time was 5h. The sintering heating, insulation and cooling process continued to be vacuumed until the insulation was completed. After cooling to room temperature, the sintered material was taken out. The material was then hot isostatically pressed at 1000℃ for 2h, with the pressure set to 100MPa, for further densification, and then cooled with the furnace.
[0037] The tensile properties of the material were tested, and the results showed that the yield strength of the material was 750MPa, the tensile strength was 800MPa, and the elongation was 15%, which showed a good match between strength and plasticity. Compared with Comparative Example 1, the yield strength of the material was significantly increased by 250MPa, and the plasticity was only reduced by 5%. The organization of the material was tested, and the results were as follows: Figure 1 and Figure 2 shown. Figure 1 It can be seen that the main morphology of the matrix Ti in the material is equiaxed, with a size of 10 to 50 μm. The reinforcements are mainly TiC and TiB, which exist in the matrix in nearly spherical and rod-like forms, respectively. Figure 1 As shown, the size is generally no larger than 10 μm and is mainly located at the grain boundary. The volume fraction of the reinforcement phase is about 3.5%. Figure 2This is an enlarged grain boundary structure diagram. It can be seen that there are nano-sized reinforcement phases at the grain boundaries. The existence of these phases will also play a significant role in improving the strength of the material. The density of the material was tested using the Archimedean drainage method, and the density of the material was 4.51g / cm 3 , which is equivalent to the density of pure titanium. The thermal conductivity of the material was tested at 100°C using the laser flash method, and the result was 17.0W / (m·K). The thermal diffusion coefficient of the material is 6.98mm 2 / s, and the specific heat capacity is 0.54J / (g·K).
[0038] Example 2
[0039] Use electronic balance to weigh 3.0g B4C powder and 997.0g hydrogenated dehydrogenated titanium powder respectively, the average particle size of B4C powder is 30nm, the particle size range of hydrogenated dehydrogenated titanium powder is 10-50μm, and the oxygen content of the selected titanium powder is 0.20wt.%. Weigh zirconia grinding balls, weight 2kg, zirconia grinding balls are composed of four different sizes of grinding balls with diameters of 1mm, 3mm, 5mm and 10mm, so that the powders can be mixed more fully. The two weighed powders are quickly transferred to a polyurethane vacuum ball milling jar, and vacuum-sealed to prevent the increase of oxygen content. Afterwards, they are installed on a planetary ball mill for ball milling, the speed of the planetary ball milling is set to 200rpm, and the ball milling program is set to rotate clockwise for 40min, pause for 20min, then switch to rotate counterclockwise for 40min, pause for 20min, and then rotate clockwise for 40min, cycle in this order, and the effective ball milling time is accumulated to 10h. Setting the forward and reverse rotation can ensure that the powder is fully mixed evenly, and setting the pause time can dissipate the heat of the ball mill to avoid excessive energy accumulation in the ball mill, resulting in cold welding, agglomeration, etc., which will cause uneven powder mixing. After the ball milling is completed, the powder is sieved, the grinding balls are removed, and the powder is sealed and packaged to isolate oxygen and avoid oxidation.
[0040] Take the ball-milled powder, put it into a rubber bag, seal it, and then perform cold isostatic pressing at a pressure of 280MPa and a holding time of 60s. After the cold isostatic pressing is completed, the blank is quickly transferred to a vacuum sintering furnace within 20min and evacuated to 10Pa. Then start heating, and start keeping warm after the temperature reaches 1000℃ for 1h. The sintering heating, insulation and cooling process continues to be vacuumed until the insulation is completed. After cooling to room temperature, take out the sintered material. The sintered material is further densified by high-temperature hot rolling.
[0041] The tensile performance test of the material showed that the yield strength of the material was 605MPa, the tensile strength was 705MPa, and the elongation was 17%. The density of the material was tested using the Archimedes drainage method, and the density of the material was 4.49g / cm 3, which is equivalent to the density of pure titanium. The thermal conductivity of the material was tested at 100°C using the laser flash method, and the result was 16.5W / (m·K). Among them, the thermal diffusion coefficient of the material is 6.56mm 2 / s, and the specific heat capacity is 0.56J / (g·K).
[0042] Example 3
[0043] Use an electronic balance to weigh 5.0g of graphite powder and 995.0g of hydrogenated dehydrogenated titanium powder, the average particle size of the graphite powder is 3μm, the particle size range of the hydrogenated dehydrogenated titanium powder is 10-50μm, and the oxygen content of the selected titanium powder is 0.15wt.%. Weigh zirconia grinding balls, weighing 2kg, the zirconia grinding balls are composed of four different sizes of grinding balls with diameters of 1mm, 3mm, 5mm and 10mm, so that the powders can be mixed more fully. The two weighed powders are quickly transferred to a polyurethane vacuum ball milling tank, and vacuum-sealed, and then installed on a planetary ball mill for ball milling. The speed of the planetary ball mill is set to 350rpm, and the ball milling program is set to rotate clockwise for 30min, pause for 15min, then switch to counterclockwise for 30min, pause for 15min, and then rotate clockwise for 30min, and cycle in this order. The effective ball milling time is accumulated to 5h. Setting the forward and reverse rotation can ensure that the powder is fully mixed evenly, and setting the pause time can dissipate the heat of the ball mill to avoid excessive energy accumulation in the ball mill, resulting in cold welding, agglomeration, etc., which will cause uneven powder mixing. After the ball milling is completed, the powder is sieved, the grinding balls are removed, and the powder is sealed and packaged to isolate oxygen and avoid oxidation.
[0044] Take the ball-milled powder, put it into a rubber bag, seal it, and then perform cold isostatic pressing at a pressure of 250MPa and a holding time of 180s. After the cold isostatic pressing is completed, the green body is quickly transferred to a vacuum sintering furnace within 60min and evacuated to 5Pa. Then start heating, and start keeping warm after the temperature reaches 950℃ for 10h. The sintering heating, insulation and cooling process continues to be vacuumed until the insulation is completed. After cooling to room temperature, take out the sintered material. The material is then hot isostatically pressed at 1000℃ for 2h to further densify it, and then cooled with the furnace.
[0045] The tensile performance test of the material showed that the yield strength of the material was 650MPa, the tensile strength was 730MPa, and the elongation was 18%. The density of the material was tested using the Archimedes drainage method, and the density of the material was 4.50g / cm 3 The thermal conductivity of the material was tested at 100°C using the laser flash method, and the result was 19.0W / (m·K). The thermal diffusion coefficient of the material is 7.26mm 2 / s, and the specific heat capacity is 0.58J / (g·K).
[0046] Example 4
[0047] Use an electronic balance to weigh 5.0g TiB2 powder, 5.0g B4C powder and 990.0g hydrogenated dehydrogenated titanium powder, the average particle size of the TiB2 powder is 500nm, the average particle size of the B4C powder is 500nm, the particle size range of the hydrogenated dehydrogenated titanium powder is 10-50μm, and the oxygen content of the selected titanium powder is 0.22wt.%. Weigh 4kg zirconia grinding balls, which are composed of four different sizes of grinding balls with diameters of 1mm, 3mm, 5mm and 10mm, so that the powders can be mixed more fully and evenly. The two weighed powders were quickly transferred to a polyurethane vacuum ball mill, evacuated and sealed, and then installed on a planetary ball mill for ball milling. The rotation speed of the planetary ball mill was set to 250 rpm, and the ball milling program was set to rotate clockwise for 30 minutes, pause for 20 minutes, then switch to counterclockwise rotation for 30 minutes, pause for 20 minutes, and then rotate clockwise for 20 minutes. This sequence was repeated, and the effective ball milling time accumulated to 5 hours.
[0048] Take the ball-milled powder, put it into a rubber bag, seal it, and then perform cold isostatic pressing at a pressure of 200MPa and a holding time of 60s. After the cold isostatic pressing is completed, the green body is quickly transferred to a vacuum sintering furnace within 10min and evacuated to 10Pa. Then start heating, and start keeping warm after the temperature reaches 1080℃ for 6h. The sintering heating, insulation and cooling process continues to be vacuumed until the insulation is completed. After cooling to room temperature, take out the sintered material. The sintered material is further densified by high-temperature die forging.
[0049] The tensile performance test of the material showed that the yield strength of the material was 750MPa, the tensile strength was 800MPa, and the elongation was 10%. The density of the material was tested using the Archimedes drainage method, and the density of the material reached 4.52g / cm 3 The thermal conductivity of the material was tested at 100°C using the laser flash method, and the result was 15.5W / (m·K), where the thermal diffusion coefficient of the material was 6.52mm 2 / s, and the specific heat capacity is 0.53J / (g·K).
[0050] Comparative Example 1
[0051] Weigh 1000.0 g of hydrogenated dehydrogenated titanium powder, the particle size of which is 10-50 μm, and the oxygen content of the selected titanium powder is 0.21 wt.%. Put the powder into a rubber bag, seal it, and then perform cold isostatic pressing at a pressure of 180 MPa for 45 seconds. After the cold isostatic pressing is completed, quickly transfer the green body to a vacuum sintering furnace within 10 minutes and evacuate it to 10 -1Pa. Then heating started, and insulation started after the temperature reached 1050℃, and the insulation time was 5h. The sintering heating, insulation and cooling process continued to be vacuumed until the insulation was completed. After cooling to room temperature, the sintered material was taken out. The material was then hot isostatically pressed at 1000℃ for 2h, with the pressure set to 100MPa, for further densification, and then cooled with the furnace.
[0052] The density of the material was tested using the Archimedes drainage method, and the density of the material reached 4.52g / cm 3 The tensile properties of the material were tested, and the results showed that the yield strength of this pure titanium material was 500MPa, the tensile strength was 605MPa, the elongation was 20%, and the thermal conductivity of the material tested at 100°C using the laser flash method was 20.1W / (m·K).
[0053] In short, through Figure 3 It can be seen from the stress-strain curves shown that although the plasticity of the composite materials prepared in Examples 1-4 is slightly lower than that in Comparative Example 1, it still maintains a high level, and the strength of the materials prepared in Examples 1-4 is greater than that in Comparative Example 1. Therefore, the composite materials obtained in Examples 1-4 achieve a balance between the mechanical properties and thermal conductivity of the material, and have the advantages of high strength, good thermal conductivity, good plasticity, and easy processing.
[0054] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A medium-strength and high thermal conductivity titanium-based composite material, characterized in that: The invention comprises a reinforcement and a pure titanium matrix, wherein the reinforcement is produced by an in-situ autogenous reaction between a composite phase and a pure titanium matrix, the size of the reinforcement is 10 nm to 10 μm, the size of the pure titanium matrix is 10 to 50 μm, the volume fraction of the reinforcement is 1 to 4%, the yield strength of the medium-strength and high-thermal-conductivity titanium-based composite material is 605 to 750 MPa, the thermal conductivity is 15.5 to 19 W / (m·K) at 100° C., and the elongation is 10 to 18%; the reinforcement is TiC and / or TiB; The method for preparing the medium-strength and high-thermal-conductivity titanium-based composite material comprises the following steps: Step 1: according to the mass ratio of composite phase powder to titanium powder of 0.3-1.0:99.7-99.0, the two powders are mixed uniformly by vacuum ball milling; the titanium powder is prepared by hydrogenation dehydrogenation method, and the oxygen content of the titanium powder is 0.15-0.22wt%; Step 2: Put the mixed powder into a rubber bag, seal it and put it into a cold isostatic press to form it, and then obtain a green body through a cold isostatic pressing process; the time from the end of the cold isostatic pressing to the transfer of the green body into the vacuum sintering furnace is controlled within 10 to 60 minutes, the sintering temperature is set to 950 to 1080°C, and the sintering time is set to 1 to 10 hours; Step 3: Transfer the formed green body into the vacuum sintering furnace quickly and evacuate to 10 -1 ~50Pa, followed by sintering, during which the vacuum state is maintained; Step 4: After the sintered material cools down in the furnace, it is taken out; Step 5: further densifying the sintered material.
2. The medium-strength and high thermal conductivity titanium-based composite material according to claim 1, characterized in that: The composite phase is one of TiB2, graphene, graphite, carbon nanotubes, B4C or a mixture of two thereof.
3. The medium-strength and high thermal conductivity titanium-based composite material according to claim 1, characterized in that: The vacuum ball milling is performed on any one of a drum ball mill, a planetary ball mill and a vibration ball mill. The vacuum ball milling uses a polyurethane ball milling jar, and the grinding balls are ZrO2 grinding balls, and the ball-to-material ratio is 2-4:
1.
4. The medium-strength and high thermal conductivity titanium-based composite material according to claim 1, characterized in that: The rotation speed of the ball mill in step 1 is set to 150-350 rpm, and the process of the ball mill is specifically set to rotate clockwise for 20-40 minutes, pause for 10-20 minutes, then continue to rotate counterclockwise for 20-40 minutes, pause for 10-20 minutes, and cycle in this order. The cumulative effective ball milling time is 5-10 hours.
5. The medium-strength and high thermal conductivity titanium-based composite material according to claim 1, characterized in that: The pressure in step 2 is set to 180-280 MPa, and the holding time is set to 30-180 s.
6. The medium-strength and high thermal conductivity titanium-based composite material according to claim 1, characterized in that: The sintered material is then subjected to a densification treatment, wherein the densification treatment is any one of die forging, hot rolling, and hot isostatic pressing.
Citation Information
Patent Citations
Novel titanium alloy having low density, high heat conduction coefficient and high strength
CN109136645A
Preparation method for high-heat conductivity titanium-based composite material
CN111763849A
Preparation method of low-content reinforcement reinforced titanium-based composite material
CN114480904A